Insights into the anticancer activity of chiral alkylidene-β-lactams and alkylidene-γ-lactams: Synthesis and biological investigation. (1st June 2022) - Alves, Américo J.S.; Alves, Nuno G.; Laranjo, Mafalda; Gomes, Clara S.B.; Cristina Gonçalves, Ana; Bela Sarmento-Ribeiro, Ana; Filomena Botelho, M.; Pinho e Melo, Teresa M.V.D.
Graphical abstract: Abstract: Chiral alkylidene-β-lactams and alkylidene-γ-lactams were synthesized and screened for their in vitro activity against four human cancer cell lines (melanoma, esophageal, lung and fibrosarcoma carcinoma). Alkylidene-β-lactams were synthesized via Wittig reaction of diverse phosphorus ylides with benzhydryl 6‐oxopenicillanate, derived from 6-aminopenicillanic acid. Moreover, novel chiral alkylidene-γ-lactams were synthesized through a multistep strategy starting from a chiral substrate (d -penicillamine). The in vitro assays allowed the identification of four compounds with IC50 values < 10 μM for A375 cell line, and three compounds with IC50 values < 10 μM for OE19 cell line. The effect of the most promising compounds on cell death mechanism, reactive oxygen species generation as well as the evaluation of their ability to act as MMP-9 inhibitors were studied. The reported results unveil the potential of alkylidene-β-lactams as anticancer agents.